Identifikasi Golongan Senyawa Flavonoid Ekstrak Etanol Daun Anting-Anting (Acalypha indica L.) - Rahmi Nurhaini; Muchson Arrosyid; Titik Susanti (STIKES MUHAMMADIYAH KLATEN, 2021)
Anting-anting leaf is one type of plant that has medicinal properties and has not been widely used by the community. Previous research stated that the ethanol extract of Anting-anting has secondary metabolite compounds such as saponins, flavonoids, alkaloids, tannins. Flavonoids are a source of antioxidants that can inhibit premature aging caused by free radicals produced by pollution. Flavonoids can be used to avoid deadly diseases including heart disease and cancer. The purpose of this study was to determine the class of flavonoid compounds present in anting-anting leaf (Acalypha indica L.). The method used in this study was a color reaction, the material used was anting-anting leaf (Acalypa indica L.), CH3COONa. , FeCl3, Na2CO3, NaOH 0.1 N, CH3COOPb, H2¬SO4. The results of this study indicate that the Anting-anting extract (Acalypa Indica L.) positively contains flavonoids of the anthocyanidin group, using Na2CO3 reagent, the color formed is green, and positive contains flavonol and flavone groups using H2SO4 and NaOH reagents, the color formed is yellow.